2019
DOI: 10.1371/journal.ppat.1007774
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach identifies direct targets of the late viral transcription complex and an expanded promoter recognition motif in Kaposi’s sarcoma-associated herpesvirus

Abstract: The structural proteins of DNA viruses are generally encoded by late genes, whose expression relies on recruitment of the host transcriptional machinery only after the onset of viral genome replication. β and γ-herpesviruses encode a unique six-member viral pre-initiation complex (vPIC) for this purpose, although how the vPIC directs specific activation of late genes remains largely unknown. The specificity underlying late transcription is particularly notable given that late gene promoters are unusually small… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…RT-qPCR-based measurements of viral RNA from the ORF68 (early) and K8.1 (late) loci confirmed that the selective absence of late proteins in the ORF66.stop infections was due to a transcriptional defect ( Figure 1F ). The moderate decrease in both the transcript and protein of early gene ORF68 is consistent with the observation that most viral transcripts are downregulated in the absence of the vPIC component ORF24 (1). We also observed less ORF6 (the ssDNA binding protein involved in viral DNA replication) in the ORF66.stop samples, which could explain the reduced levels of viral DNA replication observed in the ORF66.stop cell line ( Figure 1D-E ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…RT-qPCR-based measurements of viral RNA from the ORF68 (early) and K8.1 (late) loci confirmed that the selective absence of late proteins in the ORF66.stop infections was due to a transcriptional defect ( Figure 1F ). The moderate decrease in both the transcript and protein of early gene ORF68 is consistent with the observation that most viral transcripts are downregulated in the absence of the vPIC component ORF24 (1). We also observed less ORF6 (the ssDNA binding protein involved in viral DNA replication) in the ORF66.stop samples, which could explain the reduced levels of viral DNA replication observed in the ORF66.stop cell line ( Figure 1D-E ).…”
Section: Resultssupporting
confidence: 87%
“…It is well established that late gene transcription is licensed by the initiation of viral genome replication (15-17). Although it has been previously reported that other vTA mutants do not exhibit a defect in viral genome replication (6, 8-10), we recently reported that mutations in ORF24 result in a ∼6-fold defect in viral genome replication (1). Similarly, we find that the ORF66.stop virus has a modest ∼3-fold defect in viral genome replication that is rescued in the ORF66.MR virus ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations